The Myth of Epistemic Implicata. Issue 6 (24th October 2021) - Sander, Thorsten
Abstract: Quite a few scholars claim that many implicata are propositions about the speaker's epistemic or doxastic states. I argue, on the contrary, that implicata are generally non‐epistemic. Some alleged cases of epistemic implicature are not implicatures in the first place because they do not meet Grice's non‐triviality requirement, and epistemic implicata in general would infringe on the maxim of quantity. Epistemic implicatures ought to be construed as members of a larger family of implicature‐like phenomena.